2017
DOI: 10.1093/eurheartj/ehx030
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac protective effects of remote ischaemic preconditioning in children undergoing tetralogy of fallot repair surgery: a randomized controlled trial

Abstract: AimsRemote ischaemic preconditioning (RIPC) by inducing brief ischaemia in distant tissues protects the heart against myocardial ischaemia-reperfusion injury (IRI) in children undergoing open-heart surgery, although its effectiveness in adults with comorbidities is controversial. The effectiveness and mechanism of RIPC with respect to myocardial IRI in children with tetralogy of Fallot (ToF), a severe cyanotic congenital cardiac disease, undergoing open heart surgery are unclear. We hypothesized that RIPC can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 54 publications
3
66
0
1
Order By: Relevance
“…In our previous study in human left ventricular myocardium, we have demonstrated an association of increased STAT5 phosphorylation with cardioprotection by RIPC 21. This association of increased STAT5 phosphorylation with RIPC was recently confirmed in myocardial tissue from the right ventricular outflow tract of children undergoing cardiac surgery under cardiopulmonary bypass along with increased phosphorylation of AKT, eNOS, and STAT3 48. In the present study, however, we analyzed expression and phosphorylation of potential signaling proteins in human atrial trabeculae at only 1 time point (ie, after in vitro hypoxia/reoxygenation).…”
Section: Discussionsupporting
confidence: 57%
“…In our previous study in human left ventricular myocardium, we have demonstrated an association of increased STAT5 phosphorylation with cardioprotection by RIPC 21. This association of increased STAT5 phosphorylation with RIPC was recently confirmed in myocardial tissue from the right ventricular outflow tract of children undergoing cardiac surgery under cardiopulmonary bypass along with increased phosphorylation of AKT, eNOS, and STAT3 48. In the present study, however, we analyzed expression and phosphorylation of potential signaling proteins in human atrial trabeculae at only 1 time point (ie, after in vitro hypoxia/reoxygenation).…”
Section: Discussionsupporting
confidence: 57%
“…Pepe and colleagues performed RIPC in children as young as 1 month (average 7 months age) undergoing tetralogy of Fallot repair, and found no differences in phosphorylated Akt or STAT3 between the control and RIPC groups [97]. Yet, Wu and colleagues demonstrated significant STAT3 activation in similar clinical settings but with older children (average 10-to 11-month-old children) [98]. Long-term regular RIPC was demonstrated to increase STAT3 in arterial samples discarded from patients undergoing CABG [99].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in humans, RIPC has been shown to increase the phosphorylation of STAT5, and in rats and pigs, RIPC has been shown to increase the phosphorylation of STAT3 [14]. However, a recent study of ours in patients showed that RIPC, when applied about one hour before open heart surgery can significantly increase the cardiac phosphorylation/activation of both STAT3 and STAT5 and reduce the myocardial I/RI in children with tetralogy of Fallot [49]. It has also been shown that STAT3 played a central role in the development of postpartum cardiomyopathy [50].…”
Section: Discussionmentioning
confidence: 99%